Thrombocyteapheresis for the Treatment of Essential Thrombocythemia Presented as a Digital Ischaemia- A Case Report (Bangladesh Medical Journal, 2019)
Thrombotic manifestations of essential thrombocytosis (ET) may be a life threatening condition. The conventional cytoreductive therapy or radioisotopes may take long time to reduce the platelet counts whereas thrombocyteapheresis can reduce the count more rapidly. Here the reported case is an essential thrombocytosis presented with digital ischaemia and was managed with intermittent flow centrifugal thrombocyteapheresis combined with hydroxyurea to reduce the platelet count.Thrombocytopharesis is an effective method and safe to reduce platelet count acutely. Thrombocyteapheresis has been done for the first time for the treatment of essential thrombocythemia (ET) in BSMMU probably also in Bangladesh.Bangladesh Med J. 2017 May; 46 (2): 56-58